Fear of COVID-19, Psychological Distress, and Insomnia Severity Among a Brazilian Psychiatric Sample at the Peak of the COVID-19 Pandemic - Felipe Alckmin-Carvalho; Suzilene Lapietra; Helder Lira; António Oliveira; Henrique Pereira; Renatha El Rafihi-Ferreira (Psychiatry International)
Background: Evaluating associations between fear of COVID-19 and psychopathology in clinical samples can yield valuable insights for the formulation of public health policies and for the training of mental health professionals in future major health crises. The objectives of our study were to evaluate the following aspects among patients diagnosed with insomnia disorder during the most critical period of the COVID-19 pandemic in Brazil: (a) the frequency of symptoms of depression and anxiety, fear of COVID-19, and severity of insomnia; (b) possible gender differences in the variables analyzed; and (c) associations between fear of COVID-19, symptoms of depression and anxiety, severity of insomnia, and sociodemographic variables. Method: A total of 353 individuals who sought treatment at a psychiatric hospital in the Brazilian public health system and were diagnosed with insomnia disorder (DSM-5) participated. The following instruments were used: the Hospital Depression and Anxiety Scale, Insomnia Severity Index, Fear of COVID-19 Scale, and a sociodemographic questionnaire. The assessments were carried out via the REDCap platform between March and July 2021. Results: Mild to moderate levels of fear of COVID-19 were identified in the majority of participants. Symptoms of depression, anxiety, and insomnia were reported at a moderate level. Although all scores were higher among women, only the fear of COVID-19 reached significant differences between groups. Fear of COVID-19 was positively correlated with symptoms of depression and anxiety and with the severity of insomnia. Anxiety scores had a positive and statistically significant effect on insomnia severity and on fear of COVID-19. Being a man and performing physical activity had a negative and statistically significant effect on fear of COVID-19. Conclusions: Being a woman, being sedentary, and having symptoms of anxiety were predictors of fear of COVID-19 among participants with insomnia disorder. This finding highlights the importance of gender-sensitive public health policies for the care of patients with insomnia during future major health crises. The associations between anxiety symptoms and fear of COVID-19 and the severity of insomnia verified in our study suggest the relevance of addressing anxiety symptoms through encouraging physical activity to mitigate the severity of insomnia and fear of pathogens in patients with insomnia.